Evaluating the role of Urban Canopy Parameters in ICON TERRA_URB - Kutay Dönmez; Stavros Stagakis; Nikolai Ponomarev; Jan-Peter Schulz; Dominik Brunner (Urban Climate, 2026)

To what extent can flexibility options reduce the need for hydrogen backup power plants? - Christoph Brunner; Steffi Misconel; Philipp Hauser; Dominik Möst (Energy Policy, 2025)

Analyzing nitrogen dioxide to nitrogen oxide scaling factors for data-driven satellite-based emission estimation methods: A case study of Matimba/Medupi power stations in South Africa - Janne Hakkarainen; Gerrit Kuhlmann; Erik Koene; Diego Santaren; Sandro Meier; Maarten C. Krol; Bart J.H. van Stratum; Iolanda Ialongo; Frédéric Chevallier; Johanna Tamminen; Dominik Brunner; Grégoire Broquet (Atmospheric Pollution Research, 2024)

The Lagrangian Atmospheric Radionuclide Transport Model (ARTM) — development, description and sensitivity analysis - Robert Hanfland; Margit Pattantyús-Ábrahám; Cornelia Richter; Dominik Brunner; Christiane Voigt (Air Quality, Atmosphere & Health, 2024)
Atmospheric dispersion models are applied to describe and predict the dispersion of emitted plumes. Here, we describe the Lagrangian Atmospheric Radionuclide Transport Model (ARTM) 2.8.0 which was developed to simulate the atmospheric dispersion of the emissions of nuclear facilities under routine operation for regulatory purposes over annual time scales. ARTM includes a diagnostic wind field model and a particle dispersion model. It simulates size-dependent wet and dry deposition, plume rise and γ -cloud shine of radioactive exhaust plumes in the simulation domain. This work presents an extensive overview of the different components of the model and of the physical and mathematical concepts of ARTM. We investigate the dependence of the plume dispersion in terms of plume volume, position of maximum concentration and dry deposition rates on key input parameters such as atmospheric stability, surface roughness, zero plane displacement height, source height and the particle size in the case of particulate matter tracers. The results indicate a strong dependence of plume volume and position of the maximum concentration on the stability as well as a minor influence on surface roughness. The source height above ground level has a low impact on the plume volume as the zero plane displacement only slightly affects the position of maximum concentration. Strong turbulence under unstable conditions tends to reduce the impact of sedimentation and decreases deposition in general. This computational model serves to advance the understanding of the dispersion of radioactive plumes in the boundary layer.

Evaluation of the GRAMM/GRAL model for high-resolution wind fields in Heidelberg, Germany - Maximilian May; Simone Wald; Ivo Suter; Dominik Brunner; Sanam N. Vardag (Atmospheric Research, 2024)

Correction to: The Lagrangian Atmospheric Radionuclide Transport Model (ARTM) – development, description and sensitivity analysis - Robert Hanfland; Margit Pattantyús-Ábrahám; Cornelia Richter; Dominik Brunner; Christiane Voigt (Air Quality, Atmosphere & Health, 2024)

A high-resolution monitoring approach of urban CO2 fluxes. Part 2 – surface flux optimisation using eddy covariance observations - Stavros Stagakis; Christian Feigenwinter; Roland Vogt; Dominik Brunner; Markus Kalberer (Science of The Total Environment, 2023)

Lagrangian Particle Dispersion Models in the Grey Zone of Turbulence: Adaptations to FLEXPART-COSMO for Simulations at 1 km Grid Resolution - Ioannis Katharopoulos; Dominik Brunner; Lukas Emmenegger; Markus Leuenberger; Stephan Henne (Boundary-Layer Meteorology, 2022)
Lagrangian particle dispersion models (LPDMs) are frequently used for regional-scale inversions of greenhouse gas emissions. However, the turbulence parameterizations used in these models were developed for coarse resolution grids, hence, when moving to the kilometre-scale the validity of these descriptions should be questioned. Here, we analyze the influence of the turbulence parameterization employed in the LPDM FLEXPART-COSMO model. Comparisons of the turbulence kinetic energy between the turbulence schemes of FLEXPART-COSMO and the underlying Eulerian model COSMO suggest that the dispersion in FLEXPART-COSMO suffers from a double-counting of turbulent elements when run at a high resolution of $$1 × 1 \,\hbox {km}^2$$ 1 × 1 km 2 . Such turbulent elements are represented in both COSMO, by the resolved grid-scale winds, and FLEXPART, by its stochastic parameterizations. Therefore, we developed a new parametrization for the variations of the winds and the Lagrangian time scales in FLEXPART in order to harmonize the amount of turbulence present in both models. In a case study for a power plant plume, the new scheme results in improved plume representation when compared with in situ flight observations and with a tracer transported in COSMO. Further in-depth validation of the LPDM against methane observations at a tall tower site in Switzerland shows that the model’s ability to predict the observed tracer variability and concentration at different heights above ground is considerably enhanced using the updated turbulence description. The high-resolution simulations result in a more realistic and pronounced diurnal cycle of the tracer concentration peaks and overall improved correlation with observations when compared to previously used coarser resolution simulations (at 7 km $$× $$ × 7 km). Our results indicate that the stochastic turbulence schemes of LPDMs, developed in the past for coarse resolution models, should be revisited to include a resolution dependency and resolve only the part of the turbulence spectrum that is a subgrid process at each different mesh size. Although our new scheme is specific to COSMO simulations at $$1 × 1 \,\hbox {km}^2$$ 1 × 1 km 2 resolution, the methodology for deriving the scheme can easily be applied to different resolutions and other regional models.

Simulating urban climate at sub‐kilometre scale for representing the intra‐urban variability of Zurich, Switzerland - Gianluca Mussetti; Dominik Brunner; Jonas Allegrini; Andreas Wicki; Sebastian Schubert; Jan Carmeliet (International Journal of Climatology, 2020)
In the face of an increasing number of urban climate modelling studies performed at sub‐kilometre resolution, systematic investigations of the performance of high‐resolution urban climate simulations and their dependency on spatial resolution are still very sparse. This study investigates the impact of the scale of representation of the urban area on the urban climate simulation with a multi‐layer urban canopy model (UCM) integrated in a mesoscale numerical weather prediction model for different sub‐kilometre resolutions. The potential of using such a model system for representing the intra‐urban climate variability is explored. The weather and climate model COSMO in Climate Mode (CCLM), coupled with the multi‐layer UCM Double‐Canyon effect parameterization (CCLM‐DCEP), was used at increasing resolution from 1 km to 250 m grid spacing to simulate the pronounced heat wave event of June–July 2015 over the city of Zurich, Switzerland. Air temperature and wind speed measurements from a network of urban stations as well as surface temperatures (STs) from Landsat 7 imagery have been used to evaluate the model results. CCLM‐DCEP showed good performance against observed air temperature, ST, and wind speed in the urban area. The model performance did not change significantly with model resolution and a performance improvement with model resolution was not found. Small‐scale features such as urban parks and large railway areas started to be resolved at sub‐kilometre grid spacing. At the finest model resolution (250 m), a spatial variability in air temperature of up to 2 K and wind speed of up to 1.5 m/s was found within the grid cell of the coarsest resolution grid (1 km). CCLM‐DCEP showed the potential to represent the urban climate at the neighbourhood scale when used at high (sub‐kilometre) resolution, which is needed to support applications such as urban planning, building energy use and urban air quality.

Observations of Atmospheric Methane and Carbon Dioxide Mixing Ratios: Tall-Tower or Mountain-Top Stations? - Ines Bamberger; Brian Oney; Dominik Brunner; Stephan Henne; Markus Leuenberger; Nina Buchmann; Werner Eugster (Boundary-Layer Meteorology, 2017)